Chonic myeloid leukemia clincal, laboratory and pharmacological aspects - Souza, Bruna Freitas de; Silva, Claudia Maria Correia e; Vivan, Rosália Hernandes Fernandes (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No especial (2022): Farmácia, 2022)
Chronic Myeloid Leukemia (CML) is a hematological neoplasia where there is a malignant change and a clonal myeloproliferation in the pluripotent stem cell, generating high production of immature granulocytes. In the beginning it manifests itself in greater number asymptomatically, with the progression of the disease it can reach an accelerated phase and then a blast crisis, with characteristic and dangerous signs and symptoms. Regarding diagnostic methodologies, there is a complete blood count, where hyperleukocytosis, immature cells and an increase in eosinophil and basophil can be observed; cytogenetic, molecular and myelogram analyzes are essential for the diagnosis and monitoring of CML. Among the therapeutic options, Imatinib stands out for being effective for most patients, and has a lasting effectiveness. If resistance develops, second generation tyrosine kinase inhibitors can be used. However, despite being a devastating disease, technological advances contribute to new therapeutic measures that will contribute to a better life expectancy for patients.